Influence of behavioral factors on the propensity for indebtedness of university students - Oliveira, Silvia Franco de (Revista de Administração da UFSM, 2020)
Purpose – The purpose of this paper is to analyze the influence of behavioral factors on the propensity for indebtedness of university students. Design/methodology/approach – The study investigated a random sample of 319 students from a private university in São Paulo. Using the Modeling of Structural Equations, the behavioral factors were measured. For the data analysis, descriptive statistics and median difference tests (Mann-Whitney U test) and independence tests (Chi-square test) were performed. Findings – The findings indicate that: a) the behavior factor presents the strongest effect on the propensity to debt; b) the degree of indebtedness is influenced by sociodemographic variables (gender, race, marital status, occupation and income); c) the levels of risk perception, materialism and propensity for indebtedness are the same for indebted and non-indebted groups; d) the levels of financial behavior and rationality differ between indebted and non-indebted groups. Research limitations/implications – The data collection was carried out in a metropolitan region where the cohort surveyed has specific characteristics that make it difficult to generalize the results. Practical implications – These results may be useful in assisting: a) school leaders in the design of educational programs; b) the financial system in the development of financial strategies and products. Social implications – Educational policy makers can take action to improve the most vulnerable groups. Originality/value – The main theoretical contribution of this work was made by the integrated analysis of four different constructs on the propensity for indebtedness of university students: materialism, rationality, financial behavior and risk perception.